Envelhecimento, trabalho e aposentadoria: análise da tomada de decisão relacionada ao trabalho em adultos mais velhos - Aquino, Rafael Lemes de (2022)
Introduction: The issue of aging, life expectancy and its social impact is a question that has been raised for a long time and, as such, social policies, dialogues and studies in this area have a very recent history. However, with the epidemiological transition, the increase in the number of active older people and in the work environment is a fertile and very challenging field, having direct reflections and influences on the health of workers and society. Objective: To analyze and investigate scientific evidence of work-related decision making in older adults. Material and Methods: Two types of studies were carried out, the first being divided into two parts: 1) a scoping review, guided by the recommendations of the Joanna Briggs Institute and; 2) the second part being a methodological framework proposed by Arksey and O'Malley in order to map the available evidence on active aging in the work context. In the second, an integrative review of the literature was carried out, aiming to analyze the available scientific evidence on the factors that can influence the decision-making to anticipate or delay retirement among older workers. Results: In the first manuscript, it was shown that active aging in the context of work involves several variables such as: the structure of work, as well as the need for interventions and approaches in the workplace; in order to improve conditions to be safer; work to promote health throughout life and employment; the importance of social relationships and lifelong learning; and have safer jobs. In the second, two categories were observed: macrostructural (political, economic and social) and microstructural (work/company; worker and health and illness); bringing the factors together in two parts with: what can anticipate and what can delay the decision-making of the older worker regarding retirement. Conclusions: The most important factors that influenced the retirement decision-making process were closely related to the organization of work, interpersonal relationships in the work environment, financial conditions, activities performed, health; in addition to the social conditions and aspects of the worker's decision based on the contexts in which he is inserted and not only on his own will. In view of such findings, the prospects may be promising not only for the issue of academic and social debate, but also for promoting new perspectives and context in the face of the numerous factors found in a social reality so lacking to be applied and studied with a view to improving the understanding of the strengths and weaknesses of this population age group.